Pengembangan Media Video Pembelajaran Fisika berbahasa Kaili pada Materi Besaran Fisika dan Pengukurannya - Sahrul Saehana; Nur’azni Nur’azni; Amaruddin Hatibe (Universitas Tadulako, 2021)
The purpose of this study is to find out the activeness of students in the learning process by using video media learning physics in kaili language on the material of physics and its measurements for junior high school. This research includes a type of development research. This development uses the ADDIE model. The techniques used in data collection are questionnaires and observations. This development research process is carried out in several stages. The stages are: Analysis, Design, Development, Implementation, and Evaluation. The subject of the study for feasibility trials Of physics learning video in kaili language was conducted on students of grade VIID Hasanudin numbering 20 people at SMPN 1 Sindue. 1) Product feasibility trials are conducted by giving questionnaires in the form of questionnaires containing things related to the level of feasibility of video media learning physics in kaili language as a learning medium. The assessment results in students were obtained on average by 3.63 with the achievement of